Battery cell, battery device, and electric device
Patent Information
- Application Number
- CN202610758399.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2026-01-29
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-05-29
AI Technical Summary
但直接将二者混合形成混合体系下的电池,虽然可以在一定程度上降低成本,但是,由于充放电过程中含锂过渡金属氧化物与磷酸锰铁锂材料交互作用产生的副反应,往往会使得循环寿命难以满足实际量产需求
[0007]In the aforementioned technical solution, the mixed use of lithium transition metal oxide particles and lithium manganese iron phosphate particles offers the advantage of high energy density at low cost, thus compensating for the energy density range gap between single lithium manganese iron phosphate batteries and single lithium transition metal oxide batteries. Simultaneously, to further improve the energy density of the hybrid system battery cells, a higher content of lithium transition metal oxide is used. However, research has found that the cycle performance of the hybrid system battery cells cannot meet the requirements. Further research revealed that compared to single lithium manganese iron phosphate or lithium transition metal oxide systems, there is crosstalk between lithium manganese iron phosphate and lithium transition metal oxide in the hybrid system. Specifically, the analysis is as follows: Lithium manganese iron phosphate particles have a smaller particle size and a larger specific surface area, resulting in higher surface activity. The Mn-O bonds on the surface are more prone to side reactions in the electrolyte, generating acidic byproducts. These acidic byproducts can damage the structure of the lithium transition metal oxide (e.g., the reaction products of the side reactions with the lithium transition metal oxide lead to loss of surface activity or destruction of the surface structure), accelerating the destabilization of the lithium transition metal oxide particle surface and affecting the battery's cycle performance.
Smart Images

Figure CN122314856B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to PCT patent application PCT / CN2026 / 075671, filed on January 29, 2026, entitled “Battery Cell, Battery Device and Electrical Device”, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This application relates to the field of battery device technology, and more specifically, to a battery cell, a battery device, and an electrical device. Background Technology
[0004] Lithium manganese iron phosphate (LMFP) and lithium-containing transition metal oxides (NCMs) are two very important cathode material technologies in current power batteries. Compared to the high-cost, high-energy-density NCM batteries, LMFP batteries exhibit low cost and lower energy density. Due to the high cost of cobalt, NCM batteries are often more suitable for the high-end product market. To expand the application scenarios of NCM batteries, LMFP and NCMs are often mixed to prepare hybrid cathode materials. However, directly mixing the two to form a hybrid battery system can reduce costs to some extent, but the side reactions caused by the interaction between NCMs and LMFP materials during charging and discharging often make it difficult to meet the cycle life requirements of actual mass production. Summary of the Invention
[0005] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell, a battery device, and an electrical device that take into account both the energy density and cycle performance of the battery cell.
[0006] In a first aspect, this application provides a battery cell, including a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a positive electrode active material, which includes lithium manganese iron phosphate particles and lithium-containing transition metal oxide particles. The lithium-containing transition metal oxide includes nickel, cobalt, and manganese. The molar percentage of manganese in the lithium manganese iron phosphate is 0.3 to 0.7, where the molar percentage of manganese is the ratio of the number of moles of manganese to the total number of moles of manganese and iron. Based on the mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide is 55% to 80%. In the cross-section of the positive electrode film along the thickness direction of the positive electrode, based on the total number of lithium manganese iron phosphate particles, the percentage of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%.
[0007] In the aforementioned technical solution, the mixed use of lithium transition metal oxide particles and lithium manganese iron phosphate particles offers the advantage of high energy density at low cost, thus compensating for the energy density range gap between single lithium manganese iron phosphate batteries and single lithium transition metal oxide batteries. Simultaneously, to further improve the energy density of the hybrid system battery cells, a higher content of lithium transition metal oxide is used. However, research has found that the cycle performance of the hybrid system battery cells cannot meet the requirements. Further research revealed that compared to single lithium manganese iron phosphate or lithium transition metal oxide systems, there is crosstalk between lithium manganese iron phosphate and lithium transition metal oxide in the hybrid system. Specifically, the analysis is as follows: Lithium manganese iron phosphate particles have a smaller particle size and a larger specific surface area, resulting in higher surface activity. The Mn-O bonds on the surface are more prone to side reactions in the electrolyte, generating acidic byproducts. These acidic byproducts can damage the structure of the lithium transition metal oxide (e.g., the reaction products of the side reactions with the lithium transition metal oxide lead to loss of surface activity or destruction of the surface structure), accelerating the destabilization of the lithium transition metal oxide particle surface and affecting the battery's cycle performance.
[0008] As mentioned earlier, crosstalk between lithium manganese iron phosphate (LMP) and lithium transition metal oxide (LME) particles can disrupt the structure of LME particles. Studies have found that small LMP particles have a larger specific surface area and greater surface activity, making them more prone to side reactions and generating more acidic byproducts. This has the greatest impact on the surface stability of LME particles. Therefore, this application controls the proportion of LMP particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm to be 2% to 35%, and simultaneously controls the manganese molar ratio of LMP to be 0.3 to 0.7. This can reduce the damage of LMP particles to the surface of LME particles, improve the stability of LME particles, and thus improve battery cycle performance. In addition, it can also allow the capacity of LMP itself to be better utilized, thereby balancing the energy density of the battery.
[0009] In some implementations, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size of 50nm to 120nm is 5% to 25%. Controlling the proportion of small lithium manganese iron phosphate particles within this range can further balance the cycle performance and energy density of the battery.
[0010] In some embodiments, the molar proportion of manganese in lithium iron phosphate is 0.4 to 0.6. Controlling the molar proportion of manganese in lithium iron phosphate within this range, combined with the requirement that "the proportion of lithium iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%", can, on the one hand, reduce the damage to the surface of lithium-containing transition metal oxide particles caused by manganese leaching; on the other hand, it allows the capacity of the lithium iron phosphate material to be better utilized, thereby further balancing the cycle performance and energy density of the battery.
[0011] In some embodiments, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the proportion of lithium iron phosphate (LFP) particles with a diameter greater than 120 nm and less than or equal to 600 nm, based on the total number of LFP particles, is 65% to 98%. The fact that most LFP particles have a diameter between 120 nm and 600 nm allows for higher energy density in the battery. Furthermore, compared to smaller particles (with a diameter less than 120 nm), they have a smaller specific surface area, resulting in fewer side reactions with the electrolyte. This helps reduce the generation of acidic substances in the electrolyte, thereby reducing damage to the surface of lithium transition metal oxide particles from acidic substances and improving the battery's cycle performance. Optionally, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the proportion of LFP particles with a diameter greater than 120 nm and less than or equal to 600 nm, based on the total number of LFP particles, is 70% to 90%.
[0012] In some implementations, based on the mass of the positive electrode active material, lithium manganese iron phosphate accounts for 20% to 45% of the mass. This allows for a moderate energy density in the battery while reducing the manufacturing cost.
[0013] In some embodiments, lithium manganese iron phosphate contains a metal dopant element, which includes at least one selected from Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg. The doping of this metal element helps stabilize the Me-O bond, reduce the Jan Taylor effect, suppress manganese dissolution, and improve the system lifetime. Simultaneously, element doping helps broaden the lithium-ion diffusion channels, improving the kinetic performance of the lithium manganese iron phosphate material. Optionally, the metal dopant element is at least one selected from Al, Mg, Ti, V, and Nb.
[0014] In some embodiments, lithium manganese iron phosphate contains a metal dopant element, with the doping amount ranging from 1000 ppm to 12000 ppm. Controlling the metal dopant element within a certain range allows for the improvement of the kinetic performance of lithium manganese iron phosphate through doping, while maintaining minimal impact on the battery's energy density. Optionally, the doping amount of the metal dopant element is 3000 ppm to 8000 ppm.
[0015] In some embodiments, the chemical formula of lithium manganese iron phosphate is Li. m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Wherein, 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein, M1 includes one or more of Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of S, F, Cl, and Br.
[0016] In some embodiments, the surface of the lithium manganese iron phosphate particles also contains a carbon coating layer with a thickness of 2 nm to 20 nm. An appropriately thick carbon coating layer can improve the conductivity of lithium manganese iron phosphate. Furthermore, it can reduce the dissolution of manganese and improve the decomposition of manganese ions on the electrolyte, thereby mitigating its destructive effect on the surface of lithium-containing transition metal oxide particles and further enhancing the battery's cycle performance.
[0017] In some embodiments, the lithium manganese iron phosphate (LFP) surface also contains a carbon coating layer, with the carbon coating layer accounting for 0.5% to 3% of the total mass of the LFP particles. An appropriate mass percentage of carbon coating layer can improve the conductivity of LFP, and further reduce the dissolution of manganese, thus mitigating the decomposition of manganese ions on the electrolyte and reducing its damaging effect on the surface of lithium transition metal oxide particles, thereby further improving the battery's cycle performance.
[0018] In some embodiments, the lithium-containing transition metal oxide particles include single-crystal particles. The presence of single-crystal particles in the lithium-containing transition metal oxide particles provides high mechanical strength and structural stability under high-voltage conditions, effectively resisting volume changes and stress caused by lithium-ion insertion / extraction, thus improving the battery's cycle performance. Furthermore, based on the total number of lithium-containing transition metal oxide particles, the proportion of single-crystal particles is ≥50%, optionally ≥80%, more preferably greater than or equal to 90%, and more preferably 100%.
[0019] In some embodiments, the Dn10 of the lithium transition metal oxide particles in the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet is 0.5 μm to 2.0 μm. Dn10 refers to the particle size corresponding to the cumulative number distribution of particles reaching 10% in the cumulative distribution curve of lithium transition metal oxide particles. With the Dn10 of the lithium transition metal oxide particles within this range, the particle size of small lithium transition metal oxide particles can be controlled, so that the energy density of the battery can be met while further improving cycle performance. Optionally, the Dn10 of the lithium transition metal oxide particles in the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet is 0.8 μm to 2 μm.
[0020] In some embodiments, the Dn50 of the lithium transition metal oxide particles in the cross-section of the electrode film layer along the thickness direction of the positive electrode sheet is 1.0 μm to 4.0 μm, where Dn50 refers to the particle size corresponding to the cumulative number distribution of particles reaching 50% in the cumulative distribution curve of lithium transition metal oxide particles. Within this range, the Dn50 of the lithium transition metal oxide particles can balance the kinetics of the lithium transition metal oxide particles, improve the current shunting problem between lithium manganese iron phosphate particles and lithium transition metal oxide particles, and allow the material's capacity to be better utilized; simultaneously, it reduces the damage to lithium transition metal oxide particles caused by small lithium manganese iron phosphate particles, thereby achieving a balance between the battery's cycle performance and energy density. Optionally, the Dn50 of the lithium transition metal oxide particles in the cross-section of the positive electrode film layer along the thickness direction of the positive electrode sheet is 2.0 μm to 3.5 μm.
[0021] In some embodiments, the molar percentage of nickel in the lithium-containing transition metal oxide is 0.55 to 0.8% based on the total molar number of nickel, cobalt, and manganese. Lithium-containing transition metal oxides are medium-to-high nickel materials, resulting in higher energy density batteries.
[0022] In some embodiments, the molar percentage of nickel in the lithium-containing transition metal oxide is 0.6 to 0.75 based on the total molar number of nickel, cobalt, and manganese. Compared to low-nickel materials, medium-nickel lithium-containing transition metal oxide materials have higher energy density, and the energy density increase is more significant after the voltage is increased to 4.4V. At the same time, compared to high-nickel lithium-containing transition metal oxide materials, they have better stability. Combined with the fact that "the proportion of lithium manganese iron phosphate particles with a particle size greater than or equal to 50nm and less than or equal to 120nm is 2% to 35%", the cycle performance of the hybrid battery system can be taken into account.
[0023] In some embodiments, the molar percentage of cobalt in the lithium transition metal oxide is 0.05 to 0.3% based on the total molar number of nickel, cobalt, and manganese. Cobalt can suppress cation mixing in lithium transition metal oxide materials, improving their cycle stability. With a cobalt content within this range, when combined with lithium iron manganese phosphate (LFP) containing fewer small particles, it can reduce the likelihood of LFP damaging the surface of lithium transition metal oxide particles, improving battery cycle performance. Furthermore, it can maintain the nickel content, ensuring that the battery's energy density remains largely unaffected.
[0024] In some embodiments, the molar percentage of manganese in the lithium-containing transition metal oxide is 0.15 to 0.4% based on the total molar number of nickel, cobalt, and manganese. Manganese (and aluminum) can reduce the cost of lithium-containing transition metal oxide materials and improve their structural stability and safety performance. A manganese content within the aforementioned range can balance the structural stability and energy density of the material.
[0025] In some embodiments, the lithium-containing transition metal oxide further includes modifying elements, including one or more elements selected from Zr, La, Sr, Sb, Al, and W. The addition of modifying elements to the lithium-containing transition metal oxide material allows Zr to suppress cation mixing, increase interlayer spacing, and facilitate lithium-ion transport; La can suppress cation mixing and reduce lattice distortion, improving interface stability; Sr can stabilize interlayer spacing, reduce lattice changes, and facilitate lithium-ion transport; and Sb, with its strong electronegativity, can suppress lattice oxygen evolution and enhance the structural stability of the lithium-containing transition metal oxide material.
[0026] In some embodiments, the positive electrode film further includes a conductive agent, which includes at least one of carbon nanotubes, graphite sheets, conductive carbon black, and Ketjen black; optionally, carbon nanotubes are included. When the battery active material contains both lithium manganese iron phosphate particles and lithium-containing transition metal oxide particles (a mixed system), current shunting is prone to occur. However, the presence of carbon nanotubes in the positive electrode film helps improve electron transport in the positive electrode film, thereby effectively improving the current shunting problem during the charging and discharging of different active materials, and thus improving the cycle performance of the battery.
[0027] In some embodiments, the positive electrode film layer further includes a binder and a conductive agent. The mass ratio of the positive electrode active material, binder, and conductive agent in the positive electrode film layer is (92~99):(0.5~3):(0.5~3). When the mass ratio of these three components in the positive electrode sheet is within the above range, the battery can have a high energy density, the electrode sheet can have high stability, and it also possesses an excellent conductive network.
[0028] In some embodiments, the areal density of the positive electrode film is 200 mg / 1540 mm². 2 ~400mg / 1540mm 2 Within this range, the areal density of the positive electrode film allows for higher energy density and better kinetics in the battery. Optionally, the areal density of the positive electrode film is 240 mg / 1540 mm². 2 ~300mg / 1540mm 2 .
[0029] In some embodiments, the single-sided compaction density of the positive electrode film is 2.40 g / cm³. 3 ~3.30g / cm 3 Within this range, the single-sided compaction density of the positive electrode film can result in a higher energy density and better kinetics for the battery. Optionally, the single-sided compaction density of the positive electrode film is 2.70 g / cm³. 3 ~3.00g / cm 3 .
[0030] In some embodiments, the negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, wherein the areal density of the negative electrode film layer is 110 mg / 1540 mm². 2 ~180mg / 1540mm 2 Within this range, the areal density of the negative electrode film layer can be better matched with that of the positive electrode film layer, resulting in higher energy density for the battery. Optionally, the areal density of the negative electrode film layer is 110 mg / 1540 mm². 2 ~150mg / 1540mm 2 .
[0031] In some embodiments, the compaction density of the negative electrode film is 1.2 g / cm³. 3 ~1.7g / cm 3 .
[0032] In some embodiments, the battery cell also includes an electrolyte, which comprises chain carbonates and cyclic carbonates. Lithium manganese iron phosphate and lithium-containing transition metal oxide materials have different operating voltage platforms. Batteries in this hybrid system suffer from current shunting issues. Compared to pure lithium-containing transition metal oxide systems or pure lithium manganese iron phosphate systems, it places higher demands on kinetics and the lithium-ion transport capacity of the electrolyte. Cyclic carbonates have high dielectric constants, which can fully dissociate lithium salts and improve the conductivity of the electrolyte. However, the viscosity of cyclic carbonates is too high, affecting the liquid phase transport capacity of the electrolyte. Therefore, low-viscosity chain carbonates are used in the blend to improve the lithium-ion transport capacity of the electrolyte.
[0033] In some embodiments, based on the mass of the electrolyte, the mass percentage of chain carbonate is 55% to 65%, and the mass percentage of cyclic carbonate is 20% to 30%. By controlling the mass percentages of chain carbonate and cyclic carbonate within appropriate ranges, lithium salt can be effectively dissociated, and the viscosity of the electrolyte can be made more suitable to facilitate lithium-ion transport.
[0034] In some embodiments, the chain carbonates include methyl ethyl carbonate and diethyl carbonate; the cyclic carbonates include ethylene carbonate. Both methyl ethyl carbonate and diethyl carbonate have low viscosities, which is beneficial for adjusting the viscosity of the electrolyte, thereby increasing the lithium-ion transport capacity of the electrolyte; simultaneously, in combination with ethylene carbonate, it facilitates the dissociation of lithium salts by the electrolyte, further increasing the lithium-ion transport capacity.
[0035] In some embodiments, the electrolyte further includes a first film-forming additive, which includes one or more of lithium difluorophosphate and tris(trimethylsilane)phosphate. Crosstalk exists between lithium-containing transition metal oxides and lithium manganese iron phosphate. The oxidation potential of the first film-forming additive is lower than that of ethyl methyl carbonate and diethyl carbonate. During battery charging, it can preferentially form a dense and stable CEI film at the positive electrode, thus mitigating the crosstalk problem.
[0036] In some embodiments, the first film-forming additive accounts for 1% to 4% of the mass of the electrolyte. Adding an appropriate amount of the first film-forming additive is beneficial for forming a dense CEI film at the positive electrode, thereby improving the crosstalk problem between lithium-containing transition metal oxides and lithium manganese iron phosphate.
[0037] In some embodiments, the electrolyte further includes a second film-forming additive, which includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propanesulfonate lactone, ethylene disulfate, and butene sulfite. In the mixed system, transition metals inevitably dissolve, and these dissolved transition metals reach the negative electrode, damaging the SEI film. The aforementioned film-forming additives can form a dense SEI film, reducing the damage to the SEI film caused by transition metals.
[0038] In some embodiments, the second film-forming additive accounts for 0.2% to 2% of the mass based on the electrolyte. Adding an appropriate amount of the second film-forming additive is beneficial for forming a dense SEI film at the negative electrode, thereby mitigating the damage to the SEI film caused by transition metal ions.
[0039] In some embodiments, the electrolyte includes one or more of lithium hexafluorophosphate and lithium bisfluorosulfonylimide, optionally lithium hexafluorophosphate and lithium bisfluorosulfonylimide. Since lithium manganese iron phosphate is usually carbon-coated, water is inevitably introduced into the system. Water readily reacts with lithium hexafluorophosphate to generate HF, which disrupts the layered structure of lithium-containing transition metal oxides. The addition of lithium bisfluorosulfonylimide can reduce the amount of HF and improve the damage to lithium-containing transition metal oxides. However, lithium bisfluorosulfonylimide corrodes the positive electrode current collector under high voltage, so lithium hexafluorophosphate needs to be added in conjunction to function as a lithium salt.
[0040] In some implementations, the lithium hexafluorophosphate content is 5%-10% based on the mass of the electrolyte.
[0041] In some embodiments, the mass content of lithium bis(fluorosulfonyl)imide is 0.1%-2% based on the mass of the electrolyte.
[0042] In some embodiments, the positive electrode sheet further includes a conductive undercoat layer located between the positive current collector and the positive electrode film layer. The conductive undercoat layer protects the positive current collector, mitigating corrosion of the positive current collector by lithium bis(fluorosulfonyl)imide at high voltages and improving the battery's cycle performance.
[0043] In some embodiments, the battery cell also includes a separator located between the positive and negative electrode plates. The separator has a permeability of 450 s / 100cc to 650 s / 100cc. A higher permeability value indicates poorer permeability, which on the one hand improves the transport of lithium ions in the separator, reduces overall impedance, and improves kinetic and cycle performance; on the other hand, it can also play a partial role in isolation, preventing the transition metal generated after the lithium-containing transition metal oxide is destroyed from reaching the positive electrode and avoiding transition metal ions from passing through the separator to the negative electrode, thus affecting the SEI film.
[0044] Secondly, this application provides a battery device including any of the battery cells in the first aspect.
[0045] Thirdly, this application provides an electrical device, including the battery device of the second aspect. Attached Figure Description
[0046] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the preferred embodiments below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 This is a schematic diagram of a secondary battery according to one embodiment of this application.
[0047] Figure 2 yes Figure 1 An exploded view of a secondary battery according to one embodiment of this application is shown.
[0048] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.
[0049] Figure 4 This is a schematic diagram of a battery device according to one embodiment of this application.
[0050] Figure 5 yes Figure 4 An exploded view of a battery device according to an embodiment of this application is shown.
[0051] Figure 6 This is a schematic diagram of an electrical device that uses a secondary battery as a power source according to one embodiment of this application.
[0052] Explanation of reference numerals in the attached figures: 1-Battery assembly; 2-Upper battery box; 3-Lower battery box; 4-Battery module; 5-Battery cell; 51-Housing; 52-Electrode assembly; 53-Top cover assembly. Detailed Implementation
[0053] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0054] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0055] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0056] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0057] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0058] Currently, lithium-ion transition metal oxide (LME) batteries offer the advantage of high energy density, but the high cost of LME materials limits their widespread application. Lithium manganese iron phosphate (LMP), as an alternative to LFe, offers advantages in low cost and high cycle stability. Furthermore, compared to LFe, LMP has a higher charge / discharge voltage platform and relatively higher energy density. Theoretically, a battery combining LMP and LME (hereinafter referred to as a "hybrid system") should achieve a moderate cost, moderate energy density, and moderate cycle performance. However, research has shown that this is not the case in practice. Because the battery reaction involves continuous charging and discharging, there is an interaction between LMP and LME, which negatively impacts the cycle performance of the hybrid system. Therefore, this application provides a single battery cell that balances energy density and cycle performance.
[0059] [Battery cell] This application provides a battery cell, including a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a positive electrode active material, which includes lithium manganese iron phosphate particles and lithium-containing transition metal oxide particles. The lithium-containing transition metal oxide includes nickel, cobalt, and manganese. The molar percentage of manganese in the lithium manganese iron phosphate is 0.3-0.7, where the molar percentage of manganese is the ratio of the number of moles of manganese to the total number of moles of manganese and iron. Based on the mass of the positive electrode active material, the mass percentage of the lithium-containing transition metal oxide is 55%-80%. In a cross-section of the positive electrode film along the thickness direction of the positive electrode, based on the total number of lithium manganese iron phosphate particles, the percentage of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2%-35%.
[0060] The "cross section of the positive electrode film along the thickness direction of the positive electrode sheet" can be obtained using instruments or equipment such as a focused electron beam (FIB) microscope (non-limiting examples include the FEIScios2HiVac device), an ion sectioning polisher (non-limiting examples include the IB-09010CP argon ion sectioning polisher and the IB-19500CP ion sectioning polisher from JEOL Corporation of Japan), or plasma quenching. The electron microscope image field of view can be obtained using instruments or equipment including, but not limited to, scanning electron microscopy (SEM). Non-limiting examples of SEM instruments include the Sigma300 scanning electron microscope and the Apreo2SEM field emission scanning electron microscope from ZEISS Corporation of Germany.
[0061] The method for confirming the "mass content of lithium transition metal oxides and lithium manganese iron phosphate" includes: taking a discharged battery cell (discharged to 0% SOC at 0.33C current), disassembling the battery cell, removing the positive electrode sheet, soaking it in DMC (dimethyl carbonate) for 4 hours to remove residual electrolyte and lithium salt, and then drying it in an oven to obtain the positive electrode sheet. The positive electrode material is dispersed in ethanol solvent by a scraping method, and the sample is prepared according to the industry-standard transmission electron microscopy (TEM) sample preparation method. After successful sample preparation, it is observed under the TEM field of view. Under the auxiliary EDS surface scanning field, obvious lithium transition metal oxide particles, lithium manganese iron phosphate particles, or conventional SP particles can be seen. Particles rich in nickel and cobalt are labeled as lithium transition metal oxide particles, and particles rich in iron are labeled as lithium manganese iron phosphate particles. Using EDS to statistically analyze the Mn:Fe atomic ratio of at least five lithium manganese iron phosphate particles and the Ni:Co:Mn atomic ratio of lithium transition metal oxide particles, the average values are calculated to obtain the Mn:Fe molar ratio in lithium manganese iron phosphate particles and the Ni:Co:Mn molar ratio in lithium transition metal oxide particles. Simultaneously, for other positive electrode samples tested above, the positive electrode film layer of the positive electrode samples is peeled off, and the positive electrode film layer is thoroughly washed with acetone to remove binders and dispersants. The samples are then filtered, dried, and ground to obtain powder. 0.05g of the uniformly mixed powder was dissolved in 40ml of anhydrous ethanol, and then an appropriate amount of dispersant was added. The mixture was stirred until a suspension was obtained. 2ml of the suspension was mixed with 2ml of anhydrous ethanol and then subjected to ultrasonic treatment at a power of 480W for 5 minutes to obtain a uniformly dispersed suspension. An appropriate amount of the middle layer suspension was taken, and the contents of Ni, Mn, and Fe in the suspension were determined by inductively coupled plasma atomic emission spectrometry (ICP). Combined with the previously obtained Mn:Fe molar ratio of lithium manganese iron phosphate particles and the Ni:Co:Mn molar ratio of lithium transition metal oxide particles, the mass content of lithium manganese iron phosphate and lithium transition metal oxide in the positive electrode active material can be calculated. In addition, the content of doping elements can also be determined simultaneously.
[0062] In this application, the method for obtaining the "cross section of the positive electrode film along the thickness direction of the positive electrode sheet" is as follows: A discharged battery cell (discharged to 0% SOC at 0.33C current) is taken, and the positive electrode sheet is removed after disassembling the battery cell. It is then soaked in DMC (dimethyl carbonate) for 4 hours to remove residual electrolyte and lithium salt. Afterward, it is placed in an oven and dried to obtain the positive electrode sheet. A portion of the positive electrode sheet is cut to obtain the first positive electrode sheet sample. The positive electrode film is cut along the thickness direction of the positive electrode sheet sample using an argon ion beam (for example, an equipment model: Leica EM TIC 3X CP, operating voltage: 6kV, operating time: 6h can be used). After exposing the cross section, a scanning electron microscope (for example, an equipment model: Hitachi SU8230, operating voltage: 3kV, beam current: high, probe model: U (LA100), working distance <5mm can be used) is used to observe the cross section of the positive electrode film along the thickness direction of the positive electrode sheet. Images were acquired using a field emission scanning electron microscope (FESEM) at non-edge locations in the cross-section of the positive electrode film (after observing the edge of the positive electrode sheet under the SESEM, the field of view was adjusted to the center of the sample) in secondary electron mode. Electron microscopy images were taken at magnifications of 2kx for lithium transition metal oxide particles and 30kx for lithium manganese iron phosphate particles. The elements in the particles were then analyzed using energy-dispersive X-ray spectroscopy (EDS). Particles rich in nickel and cobalt were labeled as lithium transition metal oxide particles, and particles rich in iron were labeled as lithium manganese iron phosphate particles. The lithium manganese iron phosphate particles in the electron microscopy images were then analyzed using ImageJ software (1.46r, Win64 version). The "Feret diameter" analysis function in ImageJ was used to analyze the area of the particles in the cross-section along the thickness direction of the positive electrode film. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size.
[0063] The specific steps for using ImageJ software are as follows: Load the scanning electron microscope image to be analyzed, use the Cellpose plugin to identify particles, and then perform manual corrections. Use ImageJ to read and analyze data. The specific method for identifying particles using the Cellpose plugin is as follows: Set the segmentation diameter parameter (diameter in the Segmentation module) to 15 pixels, and click "run cyto3" to identify particles. Manually mark particles in the image that were not identified by the software, were not fully identified, or were identified incorrectly. Particles that were not identified by the software, were not fully identified, or were identified incorrectly mainly include the following: 1. Particles that are too large or have scratches on their surface, making them unidentifiable or incompletely identifiable; 2. During argon ion beam cutting, scratches may be generated on the particle surface, which the software may misinterpret as particle boundaries, leading to identification errors; 3. Particles that are too small and were not successfully identified; 4. Particles located at the edge of the electron microscope field of view, with the interior penetrated by the edge, preventing a complete view of the morphology, resulting in identification errors due to partial identification replacing the whole. For the unidentified or misidentified particles mentioned above, manual calibration is performed as follows: Particles located at the edges of the scanning electron microscope that are not fully displayed are deleted; It is determined whether other unidentified or misidentified particles have internal cracks or scratches. If no cracks or scratches are found, the particle is considered a single particle, and its boundary is manually marked based on observation; If cracks or scratches are found within the particle, it is determined whether the cracks or scratches penetrate the particle. If not, it is considered a single particle and manually marked; If the cracks or scratches penetrate the particle, it is determined whether the cracks or scratches are linear or irregular; If the cracks or scratches are irregular, they are considered the boundary between particles, and particles are divided along this boundary; If the cracks or scratches are linear, contrast is compared; If the contrast is not obvious and there is no crack-like appearance, it is considered a scratch and marked as a single particle; If the contrast is strong and there is a crack-like appearance, it is considered the boundary between particles and marked as two particles. After manual marking, irrelevant information from the automatic image processing is deleted, thus completing the particle identification and marking in the image.
[0064] In addition, multiple attached, stacked, or bonded particles can be identified and separated into multiple particles by software (based on parameters such as grayscale / contrast / brightness) or manual assistance.
[0065] Following the above method, to ensure a statistically significant sample size, at least 10 non-overlapping scanning electron microscope (SEM) images (e.g., 150 μm × 120 μm for lithium transition metal oxide particles and 5 μm × 4 μm for lithium manganese iron phosphate particles) were acquired for each positive electrode. The particle size of at least 1500 particles was then counted. These 1500 lithium manganese iron phosphate particles were arranged in ascending order of particle size to obtain the number of lithium manganese iron phosphate particles with a diameter greater than or equal to 50 nm and less than or equal to 120 nm. This number then represents the percentage of lithium manganese iron phosphate particles with a diameter greater than or equal to 50 nm and less than or equal to 120 nm based on the total number of lithium manganese iron phosphate particles.
[0066] In the aforementioned technical solution, the mixed use of lithium transition metal oxide particles and lithium manganese iron phosphate particles offers the advantage of high energy density at low cost, thus compensating for the energy density range gap between single lithium manganese iron phosphate batteries and single lithium transition metal oxide batteries. Simultaneously, to further improve the energy density of the hybrid system battery cells, a higher content of lithium transition metal oxide is used. However, research has found that the cycle performance of the hybrid system battery cells cannot meet the requirements. Further research revealed that compared to single lithium manganese iron phosphate or lithium transition metal oxide systems, there is crosstalk between lithium manganese iron phosphate and lithium transition metal oxide in the hybrid system. Specifically, the analysis is as follows: Lithium manganese iron phosphate particles have a smaller particle size and a larger specific surface area, resulting in higher surface activity. The Mn-O bonds on the surface are more prone to side reactions in the electrolyte, generating acidic byproducts. These acidic byproducts can damage the structure of the lithium transition metal oxide (e.g., the reaction products of the side reactions with the lithium transition metal oxide lead to loss of surface activity or destruction of the surface structure), accelerating the destabilization of the lithium transition metal oxide particle surface and affecting the battery's cycle performance.
[0067] As mentioned earlier, crosstalk between lithium manganese iron phosphate (LMP) and lithium transition metal oxide (LME) particles can disrupt the structure of LMEs. Studies have shown that small LMP particles have a larger specific surface area and greater surface activity, making them more prone to side reactions and generating more acidic byproducts. This has the greatest impact on the surface stability of LME particles. Therefore, this application controls the proportion of LMP particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm to be 2% to 35%, and simultaneously controls the manganese molar ratio of LMP to be 0.3 to 0.7. This avoids an excessively large proportion of small LMP particles, preventing excessive acidic byproducts from reacting with the electrolyte and damaging the LME particles, thus improving the structural stability and cycle performance of LMEs. On the other hand, it also avoids an excessively low proportion of small LMP particles, which would affect the kinetic performance of the LMP material in the mixed system and the specific capacity of LMP, thus balancing the energy density of the battery. In addition, controlling the molar ratio of manganese in lithium iron phosphate to 0.3~0.7 can prevent excessive Mn-O bonds in lithium iron phosphate from reacting with the electrolyte to generate excessive acidic byproducts, thus mitigating the damage of lithium iron phosphate to lithium-containing transition metal oxide particles and improving the cycle performance of the battery cells. At the same time, it can also take into account the capacity of lithium iron phosphate and the energy density of the battery.
[0068] As an example, the molar ratio of manganese in lithium iron phosphate is 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, or 0.7, or any value within either of these ranges. Optionally, the molar ratio of manganese in lithium iron phosphate is 0.4 to 0.6. Controlling the molar ratio of manganese in lithium iron phosphate within this range, in conjunction with the requirement that "the proportion of lithium iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%", can, on the one hand, reduce the damage to the surface of lithium-containing transition metal oxide particles caused by manganese leaching; on the other hand, it can allow the capacity of the lithium iron phosphate material to be better utilized, thereby further balancing the cycle performance and energy density of the battery.
[0069] As an example, the proportion of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2%, 5%, 10%, 15%, 20%, 25%, 30%, or 35%, or any value within either of these ranges. Optionally, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size of 50 nm to 120 nm is 5% to 25%. Controlling the proportion of small lithium manganese iron phosphate particles within this range can further balance the cycle performance and energy density of the battery.
[0070] Those skilled in the art can control the particle size of lithium manganese iron phosphate (LMP) particles using any known process. For example, the nucleation and growth of LMP particles can be controlled by adjusting the grinding particle size, temperature, and time during the LMP preparation process. The mechanical force of crushing and grinding processes can be used to process the raw material to the target particle size distribution range, thus adjusting the particle size. Alternatively, screening and grading equipment can be used to separate the particle size distribution, obtaining the required particle size ratio. Equipment parameters such as the grading frequency of air-crushing equipment can also help control the particle size.
[0071] As an example, based on the mass of the positive electrode active material, the mass percentage of lithium transition metal oxide is 55%, 60%, 65%, 70%, 75%, or 80%, or any value within either of these ranges. Optionally, based on the mass of the positive electrode active material, the mass percentage of lithium transition metal oxide is 55% to 70%. This allows for a moderate energy density in the battery while reducing its manufacturing cost.
[0072] In some embodiments, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the proportion of lithium manganese iron phosphate particles with a diameter greater than 120 nm and less than or equal to 600 nm, based on the total number of lithium manganese iron phosphate particles, is 65% to 98%. The majority of lithium manganese iron phosphate particles have a diameter between 120 nm and 600 nm, which allows for higher energy density in the battery. Furthermore, compared to smaller particles (with a diameter less than 120 nm), they have a smaller specific surface area and fewer side reactions with the electrolyte, which helps reduce the generation of acidic substances in the electrolyte. This reduces damage to the surface of lithium-containing transition metal oxide particles from acidic substances, thereby improving the battery's cycle performance.
[0073] As an example, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a diameter greater than 120 nm and less than or equal to 600 nm is 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 98%, or any value within either of these ranges. Optionally, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a diameter greater than 120 nm and less than or equal to 600 nm is 70% to 90%.
[0074] In some embodiments, based on the mass of the positive electrode active material, lithium manganese iron phosphate accounts for 20% to 45% of the mass. This can make the battery's energy density more moderate while reducing the battery's manufacturing cost.
[0075] As an example, based on the mass of the positive electrode active material, the mass percentage of lithium manganese iron phosphate is 20%, 25%, 30%, 35%, 40%, or 45%, and any value within either of these ranges.
[0076] In this application, the chemical formula of lithium manganese iron phosphate is Li. m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Wherein, 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein, M1 includes one or more of Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of S, F, Cl, and Br.
[0077] In the formulas 0≤b1≤0.1, 0≤c1≤0.1, and 0≤d1≤0.1, the values of b1, c1, and d1 can be 0, meaning that there can be no doping of M1, O1, and N1 elements. Of course, doping can also be performed in other embodiments.
[0078] In some embodiments, lithium manganese iron phosphate contains a metal dopant element (i.e., element M1 in the aforementioned chemical formula), with a doping amount of 1000 ppm to 12000 ppm. The doping amount can also be obtained using the aforementioned TEM+EDS testing method, measuring the dopant element content in more than 200 lithium manganese iron phosphate particles and calculating the average value. By controlling the metal dopant element within a certain range, the kinetic performance of lithium manganese iron phosphate can be improved through metal doping, while the energy density of the battery remains essentially unaffected.
[0079] As an example, the doping amount of the metal dopant is 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, 6000 ppm, 7000 ppm, 8000 ppm, 9000 ppm, 10000 ppm, or 12000 ppm, or any value within either of these ranges. Optionally, the doping amount of the metal dopant is between 3000 ppm and 8000 ppm.
[0080] In some embodiments, lithium manganese iron phosphate contains a metal dopant element, which includes at least one selected from Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg. The doping of this metal element helps stabilize the Me-O bond, reduce the Jan Taylor effect, suppress manganese dissolution, and improve the system lifetime. Simultaneously, element doping helps broaden the lithium-ion diffusion channels, improving the kinetic performance of the lithium manganese iron phosphate material. Optionally, the metal dopant element is at least one selected from Al, Mg, Ti, V, and Nb.
[0081] In this application, the lithium manganese iron phosphate surface also contains a carbon coating layer with a thickness of 2 nm to 20 nm. An appropriately thick carbon coating layer can improve the conductivity of lithium manganese iron phosphate. Furthermore, it can reduce the dissolution of manganese, improve the decomposition of manganese ions on the electrolyte, and thus reduce its damage to the surface of lithium-containing transition metal oxide particles, thereby further improving the battery's cycle performance.
[0082] In the SEM images of the cross-section of the aforementioned positive electrode, lithium manganese iron phosphate particles were identified (at least 10 fields of view were collected for each positive electrode, and the field of view size for counting lithium manganese iron phosphate particles was 5μm×4μm). An amorphous coating layer on the surface of the lithium manganese iron phosphate particles could be directly observed through transmission electron microscopy (TEM). Through EDS analysis, this coating layer was identified as a carbon coating layer, and the thickness of the carbon coating layer was obtained through TEM (the thickness can be obtained by averaging 10 points around the circumference of each particle to get the thickness of the carbon coating layer of each particle, and then averaging at least 10 particles to get the thickness of the carbon coating layer of the lithium manganese iron phosphate particles).
[0083] It should be noted that the carbon coating layer in this application can partially or completely coat lithium manganese iron phosphate; this application does not impose any limitation on this.
[0084] As an example, in the lithium manganese iron phosphate single particle containing a carbon coating, the thickness of the carbon coating is 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 20nm, and any value within the two numerical ranges thereof.
[0085] In some embodiments, the lithium manganese iron phosphate (LFP) surface also contains a carbon coating layer, with the carbon coating layer accounting for 0.5% to 3% of the total mass of the LFP and its surface. An appropriate mass percentage of carbon coating layer can improve the conductivity of LFP, and further reduce manganese leaching, thus mitigating the decomposition of manganese ions on the electrolyte and reducing their damaging effect on the surface of lithium transition metal oxide particles, thereby further improving the battery's cycle performance.
[0086] As an example, in a single lithium manganese iron phosphate particle containing a carbon coating, the mass percentage of the carbon coating is 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%, or any value within either of these ranges.
[0087] It should be noted that, in this application, the particle size of the aforementioned lithium manganese iron phosphate particles refers to: if the surface of lithium manganese iron phosphate does not contain a carbon coating layer, then the particle size is the diameter of the lithium manganese iron phosphate particle; if the surface of lithium manganese iron phosphate contains a carbon coating layer, then the particle size is the diameter of the particle formed by the lithium manganese iron phosphate core and the carbon coating layer.
[0088] In some embodiments, the lithium-containing transition metal oxide particles include single-crystal particles. The presence of single-crystal particles in the lithium-containing transition metal oxide particles results in fewer side reactions under high-voltage conditions, higher mechanical strength, and structural stability. This effectively resists volume changes and stress caused by lithium-ion insertion / extraction, thereby improving the battery's cycle performance.
[0089] The term "particle" refers to a particle in the positive electrode film layer that has a identifiable complete boundary in the field of view at a certain magnification, such as 10,000x. Defects and scratches may exist inside the particle, but a complete boundary sufficient to divide the particle cannot be identified inside. "Single-crystal particle" refers to an irregular aggregate state composed of one or a few particles; "polycrystalline particle" refers to a state in which dozens to hundreds of particles are aggregated together to form a spherical cross-section.
[0090] The method for testing the proportion of single-crystal particles is as follows: In the SEM images of the cross-section of the aforementioned positive electrode sheet, identify lithium-containing transition metal oxide particles (at least 10 fields of view are collected for each positive electrode sheet, with a field size of 150μm × 120μm when counting lithium-containing transition metal oxide particles). Analyze the lithium-containing transition metal oxide particles in the SEM images using ImageJ software (1.46r, Win64 version) to identify the number of single-crystal and polycrystalline particles. Based on this, the proportion of single-crystal particles can be calculated. The usage of ImageJ software is described above and will not be repeated here.
[0091] As an example, based on the total number of lithium transition metal oxide particles, the percentage of single-crystal particles is 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 100%, or any value within either of these ranges. Optionally, based on the total number of lithium transition metal oxide particles, the percentage of single-crystal particles is ≥50%, further ≥80%, even further ≥90%, and still further 100%.
[0092] In some embodiments, the Dn10 of the lithium transition metal oxide particles in the cross-section along the thickness direction of the positive electrode film is 0.5 μm to 2.0 μm. Dn10 refers to the particle size corresponding to the cumulative number distribution of particles reaching 10% in the cumulative distribution curve of lithium transition metal oxide particles. With the Dn10 of the lithium transition metal oxide particles within this range, the particle size of small lithium transition metal oxide particles can be controlled, thereby achieving the required energy density of the battery while further improving cycle performance.
[0093] As an example, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn10 of the lithium transition metal oxide particles is 0.5 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.8 μm, 2.0 μm, or any value within either of these ranges. Optionally, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn10 of the lithium transition metal oxide particles is 0.8 μm to 2 μm.
[0094] In some embodiments, the density (Dn50) of lithium transition metal oxide (LiMO) particles in the cross-section along the thickness direction of the positive electrode film is 1.0 μm to 4.0 μm. Dn50 refers to the particle size at which the cumulative number of LiMO particles reaches 50% in the cumulative distribution curve of LiMO particles. Within this range, the Dn50 of the LiMO particles can balance the kinetics of the LiMO particles, improve the current shunting problem between LiFePO4 particles and LiMO particles, and allow the material's capacity to be better utilized. Simultaneously, it reduces the damage to LiMO particles caused by small LiFePO4 particles, thereby achieving a balance between battery cycle performance and energy density.
[0095] As an example, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn50 of the lithium transition metal oxide particles is 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, or any value within either of these ranges. Optionally, in a cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn50 of the lithium transition metal oxide particles is 2.0 μm to 3.5 μm. Wherein, the value of Dn50 is greater than the value of Dn10.
[0096] The test method for "particle size of lithium transition metal oxide particles" is as follows: In the SEM images of the cross-section of the aforementioned positive electrode sheet, identify lithium transition metal oxide particles (at least 10 fields of view are collected for each positive electrode sheet, with a field size of 150 μm × 120 μm for counting lithium transition metal oxide particles). Analyze the lithium transition metal oxide particles in the SEM images using ImageJ software (1.46r, Win64 version). Use the "Feret diameter" analysis function in ImageJ to analyze the area of the particles in the cross-section along the thickness direction of the positive electrode film. According to the software manual (ImageJ User Guide IJ 1.46r), the obtained "Feret" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. The "How to use ImageJ software" is described above and will not be repeated here.
[0097] The particle size of lithium transition metal oxide particles is obtained by the aforementioned method. At least 1,500 lithium transition metal oxide particles are arranged in ascending order of particle size, and a cumulative distribution curve of the number of lithium transition metal oxide particles is plotted. Dn90, Dn10, and Dn50 refer to the particle size corresponding to the cumulative particle size concentration of the number of particles reaching 90%, 50%, and 10% in the cumulative distribution curve of the number of lithium transition metal oxide particles.
[0098] It should be noted that existing technologies typically use laser particle size analyzers to statistically analyze the particle size of lithium-containing transition metal oxide particles via Malvern laser diffraction. However, the applicant's research indicates that lithium-containing transition metal oxides may exhibit agglomeration of fewer than five particles to form granular particles (collectively referred to as near-single crystals) (due to the preparation method). Furthermore, Malvern laser diffraction testing of lithium-containing transition metal oxide particles may also reveal agglomeration of multiple small particles (an agglomeration phenomenon observed in powder material testing). Both of these factors lead to the Malvern laser diffraction results often representing the average value of the lithium-containing transition metal oxide particles and agglomerates, failing to accurately reflect the particle size of the lithium-containing transition metal oxide particles, and even more so, failing to reflect the lithium-ion diffusion path of the lithium-containing transition metal oxide particles. The Dv50 particle size obtained by this test deviates from the actual particle size and cannot truly reflect the length of the solid-phase path of lithium-containing transition metal oxide particles (generally, the solid-phase path of real particles is the length of a single particle). It also cannot accurately reflect the lithium insertion / extraction capability of lithium-containing transition metal oxide particles. Therefore, the particle size obtained by the Malvern laser diffraction method cannot be equivalent to or analogous to the particle size obtained by the statistics of the embodiments of this application.
[0099] Those skilled in the art can control the particle size of primary lithium transition metal oxide particles using any known process. For example, the growth rate and time of the lithium transition metal oxide precursor can be controlled by adjusting the temperature and time during the preparation process. The particle size can be adjusted by utilizing the mechanical force of crushing and grinding processes to process the raw material to the target particle size distribution range; particle size separation can be achieved by using sieving and grading equipment to obtain the required particle size distribution; and precise control of the feed rate, adjusting the residence time and stress state of the particles within the equipment, also helps to control the particle size.
[0100] In some embodiments, the molar percentage of nickel in the lithium-containing transition metal oxide is 0.55 to 0.8% based on the total molar number of nickel, cobalt, and manganese. The lithium-containing transition metal oxide is a medium-to-high nickel material, resulting in higher energy density in the battery.
[0101] As an example, based on the total molar number of nickel, cobalt, and manganese, the molar percentage of nickel is 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, or any value within either of these ranges. Optionally, in the lithium-containing transition metal oxide, based on the total molar number of nickel, cobalt, and manganese, the molar percentage of nickel is 0.6 to 0.75. Compared to low-nickel materials, medium-nickel lithium-containing transition metal oxide materials have higher energy density, and the energy density increase is more significant after the voltage is increased to 4.4V. Furthermore, compared to high-nickel lithium-containing transition metal oxide materials, they exhibit better stability. Combined with a "2% to 35% proportion of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm," the cycle performance of the hybrid battery system can be considered.
[0102] In some embodiments, the molar percentage of cobalt in the lithium-containing transition metal oxide is 0.05 to 0.3% based on the total molar number of nickel, cobalt, and manganese. Cobalt can suppress cation mixing in the lithium-containing transition metal oxide material, improving its cycle stability. Within this range, when combined with lithium iron manganese phosphate (LFP) with a lower particle content, it can reduce the likelihood of LFP damaging the surface of the lithium-containing transition metal oxide particles, improving battery cycle performance. Furthermore, it can maintain the nickel content, ensuring that the battery's energy density remains largely unaffected. As an example, the molar percentage of cobalt in the lithium-containing transition metal oxide material is 0.05, 0.1, 0.15, 0.2, 0.25, or 0.3%, or any value within either of these ranges.
[0103] In some embodiments, the molar percentage of manganese in the lithium-containing transition metal oxide is 0.15 to 0.4% based on the total molar number of nickel, cobalt, and manganese. Manganese (and aluminum) can reduce the cost of lithium-containing transition metal oxide materials and improve their structural stability and safety performance. A manganese content within the aforementioned range can balance the material's structural stability and energy density. As an example, the molar percentage of manganese in the lithium-containing transition metal oxide material is 0.15, 0.2, 0.25, 0.3, 0.35, or 0.4%, or any value within either of these ranges.
[0104] In some embodiments, the lithium-containing transition metal oxide further includes modifying elements, including one or more elements selected from Zr, La, Sr, Sb, Al, and W. The addition of modifying elements to the lithium-containing transition metal oxide material allows Zr to suppress cation mixing, increase interlayer spacing, and facilitate lithium-ion transport; La can suppress cation mixing and reduce lattice distortion, improving interface stability; Sr can stabilize interlayer spacing, reduce lattice changes, and facilitate lithium-ion transport; and Sb, with its strong electronegativity, can suppress lattice oxygen evolution and enhance the structural stability of the lithium-containing transition metal oxide material.
[0105] During the charging and discharging process of a battery, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of cathode materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. When the cathode material is applied to the battery system, the molar Li content changes after charge-discharge cycles.
[0106] In the examples of cathode materials in this application, the molar content of O is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of O will fluctuate.
[0107] In some embodiments, the positive electrode film layer further includes a conductive agent, the conductive agent comprising 0.5% to 3% of the positive electrode film layer by mass. The conductive agent includes at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Adding a conductive agent to the positive electrode film layer can construct an electron conduction pathway, forming a conductive network, which is beneficial for improving the utilization rate of the positive electrode active material, thereby increasing the energy density of the battery; it can also improve the electron transport rate, thus improving the rate performance of the battery. As an example, the mass percentage of the conductive agent in the positive electrode film layer is 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%, or any value within either of these ranges.
[0108] In this application, the positive electrode film layer also includes a conductive agent, which includes carbon nanotubes, and the mass percentage of carbon nanotubes in the positive electrode film layer is 0.5% to 3%. When the battery active material contains both lithium manganese iron phosphate particles and lithium transition metal oxide particles (mixed system), current shunting is likely to occur. However, the presence of carbon nanotubes in the positive electrode film layer helps to improve electron transport in the positive electrode film layer, thereby effectively improving the current shunting problem during the charging and discharging of different active materials, and thus improving the cycle performance of the battery.
[0109] As an example, the mass percentage of carbon nanotubes in the positive electrode film is 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%, or any value within either of these ranges.
[0110] Optionally, the conductive agent in the positive electrode film includes carbon nanotubes and conductive carbon black, with the carbon nanotubes accounting for 0.5% to 1.5% of the mass of the positive electrode film and the conductive carbon black accounting for 0.5% to 1.5% of the mass of the positive electrode film. By combining carbon nanotubes and conductive carbon black to form a conductive network, it is easier to improve the electron transport of the positive electrode film in the hybrid system, while also taking cost into consideration.
[0111] In some embodiments, the positive electrode film layer further includes a binder and a conductive agent. The mass ratio of the positive electrode active material, binder, and conductive agent in the positive electrode film layer is (92~99):(0.5~3):(0.5~3). When the mass ratio of these three components in the positive electrode sheet is within the above range, the battery can achieve high energy density, the electrode sheet can achieve high stability, and it also possesses an excellent conductive network. The positive electrode active material here includes lithium manganese iron phosphate, lithium-containing transition metal oxides, and optionally other positive electrode active materials mentioned above, where the mass percentage of other positive electrode active materials in the positive electrode active material is ≤10%.
[0112] In this application, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin. In other embodiments, the positive electrode film layer may also contain other substances, such as dispersants, etc., which are not limited in this application.
[0113] In some embodiments, the areal density of the positive electrode film is 200 mg / 1540 mm². 2 ~400mg / 1540mm 2 Within this range, the areal density of the positive electrode film can result in a high energy density and good kinetics for the battery. For example, the areal density of the positive electrode film is 200 mg / 1540 mm². 2 220mg / 1540mm2 240mg / 1540mm 2 200mg / 1540mm 2 260mg / 1540mm 2 280mg / 1540mm 2 300mg / 1540mm 2 320mg / 1540mm 2 350mg / 1540mm 2 Or 400mg / 1540mm 2 , and any value within its two numerical ranges. Optionally, the areal density of the positive electrode film is 240 mg / 1540 mm². 2 ~300mg / 1540mm 2 .
[0114] In some embodiments, the single-sided compaction density of the positive electrode film is 2.40 g / cm³. 3 ~3.30g / cm 3 Within this range, the single-sided compaction density of the positive electrode film can result in a high energy density and good kinetics for the battery. For example, the single-sided compaction density of the positive electrode film is 2.40 g / cm³. 3 2.60g / cm 3 2.80g / cm 3 3.00g / cm 3 Or 3.30g / cm 3 , and any value within its two numerical ranges. Optionally, the single-sided compaction density of the positive electrode film is 2.70 g / cm³. 3 ~3.00g / cm 3 .
[0115] In this embodiment, the single-sided surface density and single-sided compaction density of the positive electrode sheet can be calculated using the following formulas: Single-sided compaction density = Single-sided surface density / Thickness of the positive electrode film layer; Single-sided surface density = Coated dry weight of the positive electrode film layer / Area of the positive electrode film layer. For example, the single-sided compaction density of the positive electrode sheet can be tested using the following method: After discharging (to 0% SOC), the battery cell is disassembled to obtain the positive electrode sheet. Assuming the positive electrode sheet is single-sided coated (if it is double-sided coated, the positive electrode film layer on one side can be wiped off first), it is punched into a small circular piece with an area of S1, its weight is weighed and recorded as M1, and its thickness H1 is measured. Then, the positive electrode film layer of the positive electrode sheet is wiped off, the weight of the positive current collector is weighed and recorded as M0, and its thickness H0 is measured. Single-sided surface density = (M1-M0) / S1; Single-sided compaction density = (M1-M0) / S1(H1-H0).
[0116] In some implementations, the operating voltage of a single battery cell is 2.5V to 4.4V.
[0117] In this application, the positive current collector in the positive electrode sheet can be a metal foil or a composite current collector. For example, aluminum foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0118] In some embodiments, the positive electrode sheet further includes a conductive undercoat layer located between the positive current collector and the positive electrode film layer. The conductive undercoat layer protects the positive current collector, mitigating corrosion of the positive current collector by lithium bis(fluorosulfonyl)imide under high voltage and improving the battery's cycle performance.
[0119] The conductive primer coating comprises a binder and a conductive agent. Optionally, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, superconducting carbon, conductive graphite, acetylene black, Ketjen black, carbon dots, graphene, and carbon nanofibers. The binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene polymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid, and fluorinated acrylate resins. In the conductive primer coating, the mass ratio of binder to conductive agent is (1.5-2.5):1. The thickness of the conductive primer coating is 0.8 μm to 2 μm.
[0120] After introducing the positive electrode sheet, the preparation method of the positive electrode sheet is explained. For example, the components used to prepare the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0121] In this application, the battery cell also includes an electrolyte, which comprises chain carbonates and cyclic carbonates. Lithium manganese iron phosphate and lithium-containing transition metal oxide materials have different operating voltage platforms. The battery in this hybrid system suffers from current shunting. Compared to pure lithium-containing transition metal oxide systems or pure lithium manganese iron phosphate systems, it has higher requirements for kinetics and the lithium-ion transport capacity of the electrolyte. Cyclic carbonates have high dielectric constants, which can fully dissociate lithium salts and improve the conductivity of the electrolyte. However, the viscosity of cyclic carbonates is too high, affecting the liquid phase transport capacity of the electrolyte. Therefore, low-viscosity chain carbonates are used in the blend to improve the lithium-ion transport capacity of the electrolyte.
[0122] Optionally, based on the mass of the electrolyte, the mass percentage of chain carbonate is 55%~65%, and the mass percentage of cyclic carbonate is 20%~30%. By controlling the mass percentages of chain carbonate and cyclic carbonate within appropriate ranges, lithium salt can be effectively dissociated, and the viscosity of the electrolyte can be made more suitable to facilitate lithium-ion transport.
[0123] As an example, the mass percentage of chain carbonates in the electrolyte is 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, or 65%, or any value within either of these ranges. The mass percentage of cyclic carbonates in the electrolyte is 20%, 22%, 24%, 26%, 28%, or 30%, or any value within either of these ranges.
[0124] In some embodiments, the chain carbonates include methyl ethyl carbonate and diethyl carbonate; the cyclic carbonates include ethylene carbonate. Both methyl ethyl carbonate and diethyl carbonate have low viscosities, which is beneficial for adjusting the viscosity of the electrolyte, thereby increasing the lithium-ion transport capacity of the electrolyte; simultaneously, when combined with ethylene carbonate, it facilitates the dissociation of lithium salts by the electrolyte, further increasing the lithium-ion transport capacity.
[0125] In other embodiments, in addition to the solvents described above, a small amount of other solvents (other solvents with a mass percentage ≤10%) may be added to the electrolyte. For example, other solvents include at least one of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0126] In some embodiments, the electrolyte further includes a first film-forming additive, which includes one or more of lithium difluorophosphate and tris(trimethylsilane)phosphate. Crosstalk exists between lithium-containing transition metal oxides and lithium manganese iron phosphate. The oxidation potential of the first film-forming additive is lower than that of ethyl methyl carbonate and diethyl carbonate. During battery charging, it can preferentially form a dense and stable CEI film at the positive electrode, thus mitigating the crosstalk problem.
[0127] Optionally, based on the mass of the electrolyte, the first film-forming additive accounts for 1% to 4% of the total mass. Adding an appropriate amount of the first film-forming additive is beneficial for forming a dense CEI film at the positive electrode, thereby improving the crosstalk problem between lithium-containing transition metal oxides and lithium manganese iron phosphate. As an example, the mass percentage of the first film-forming additive in the electrolyte is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or any value within either of these ranges.
[0128] In some embodiments, the electrolyte further includes a second film-forming additive, which includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propanesulfonate lactone, ethylene disulfate, and butene sulfite. In the mixed system, transition metals inevitably dissolve, and these dissolved transition metals reach the negative electrode, damaging the SEI film. The aforementioned film-forming additives can form a dense SEI film, reducing the damage to the SEI film caused by transition metals.
[0129] In some embodiments, the mass percentage of the second film-forming additive in the electrolyte is 0.2% to 2%. Adding an appropriate amount of the second film-forming additive is beneficial for forming a dense SEI film at the negative electrode, thereby mitigating the damage to the SEI film caused by transition metal ions. As an example, the mass percentage of the second film-forming additive in the electrolyte is 0.2%, 0.5%, 1%, 1.5%, 2%, or any value within either of these ranges.
[0130] In some embodiments, the electrolyte includes one or more of lithium hexafluorophosphate and lithium bisfluorosulfonylimide, optionally lithium hexafluorophosphate and lithium bisfluorosulfonylimide (electrolyte salt). Since lithium manganese iron phosphate is usually carbon-coated, water is inevitably introduced into the system. Water readily reacts with lithium hexafluorophosphate to generate HF, which disrupts the layered structure of lithium-containing transition metal oxides. The addition of lithium bisfluorosulfonylimide can reduce the amount of HF and improve the damage to lithium-containing transition metal oxides. However, lithium bisfluorosulfonylimide corrodes the positive electrode current collector under high voltage, so lithium hexafluorophosphate needs to be added synergistically to function as a lithium salt.
[0131] In some embodiments, the mass content of lithium hexafluorophosphate is 5%-10% based on the mass of the electrolyte. As an example, the mass percentage of lithium hexafluorophosphate in the electrolyte is 5%, 6%, 7%, 8%, 9%, 10%, or any value within either of these ranges.
[0132] In some embodiments, the mass content of lithium bisfluorosulfonylimide is 0.1%-2% based on the mass of the electrolyte. As an example, the mass percentage of lithium bisfluorosulfonylimide in the electrolyte is 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, or any value within either of these ranges.
[0133] In other embodiments, the electrolyte salt in the electrolyte may also include a small amount of other electrolyte salts (the other electrolyte salts account for ≤0.2% of the mass of the electrolyte), and the other electrolyte salts include at least one of lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0134] The testing methods for each component in the electrolyte are based on the national standard GB / T 6041-2020. Specific testing steps are as follows: Disassemble the fully discharged battery in a dry glove box, take approximately 100 mL of the fully discharged electrolyte sample in a dry, clean, corrosion-resistant sample bottle, and use mass spectrometry to test the content of each component in the electrolyte, calculating the mass percentage of each component in the electrolyte.
[0135] In this application, the battery cell further includes a negative electrode sheet, which includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a negative electrode active material. As an example, the negative current collector has two opposite sides in its own thickness direction, and the negative electrode film layer is disposed on either or both of the opposite sides of the negative current collector.
[0136] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, and tin-based materials. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0137] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0138] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0139] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0140] In this application, the mass ratio of negative electrode active material, binder and conductive agent in the negative electrode film layer is (92~99):(0.5~3):(0.5~3). In the negative electrode sheet, the mass ratio of the three is within the above range, which can make the battery have a high energy density, make the electrode sheet more stable, and also have an excellent conductive network.
[0141] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0142] In other embodiments, the negative current collector of the negative electrode sheet may typically include a current collector body and a base coating. The base coating may be disposed on at least one side of the current collector body. The base coating basically does not contain negative electrode active material, but may include a small amount of carbon material. However, the carbon material forms a thin coating and cannot play the role of negative electrode active material.
[0143] In some embodiments, the areal density of the negative electrode film is 110 mg / 1540 mm². 2 ~180mg / 1540mm 2 Within this range, the areal density of the negative electrode film layer can be better matched with that of the positive electrode film layer, resulting in higher energy density of the battery. For example, the areal density of the negative electrode film layer is 110 mg / 1540 mm². 2 120mg / 1540mm2 140mg / 1540mm 2 160mg / 1540mm 2 180mg / 1540mm 2 , and any value within its two numerical ranges. Optionally, the areal density of the negative electrode film is 110 mg / 1540 mm². 2 ~150mg / 1540mm 2 .
[0144] In some embodiments, the compaction density of the negative electrode film is 1.2 g / cm³. 3 ~1.7g / cm 3 As an example, the compaction density of the negative electrode film is 1.2 g / cm³. 3 1.4g / cm 3 1.6g / cm 3 1.7g / cm 3 , and any value within its two numerical ranges.
[0145] In this embodiment, the single-sided surface density and single-sided compaction density of the negative electrode sheet can be calculated using the following formulas: Single-sided compaction density = Single-sided surface density / Thickness of the positive electrode film layer; Single-sided surface density = Coated dry weight of the negative electrode film layer / Area of the negative electrode film layer. For example, the single-sided compaction density of the negative electrode sheet can be tested using the following method: After discharging (to 0% SOC), the battery cell is disassembled to obtain the negative electrode sheet. Assuming the negative electrode sheet is single-sided coated (if it is double-sided coated, the negative electrode film layer on one side can be wiped off first), it is punched into a small circular piece with an area of S1, its weight is weighed and recorded as M1, and its thickness H1 is measured. Then, the positive electrode film layer of the negative electrode sheet is wiped off, the weight of the negative current collector is weighed and recorded as M0, and its thickness H0 is measured. Single-sided surface density = (M1-M0) / S1; Single-sided compaction density = (M1-M0) / S1(H1-H0).
[0146] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder, and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry. The negative electrode slurry is then coated onto a negative electrode current collector, and after drying, cold pressing, and other processes, the negative electrode sheet is obtained.
[0147] In this application, the battery cell also includes a separator. This application does not have any particular restrictions on the type of separator, and any well-known porous structure separator with good chemical and mechanical stability can be selected.
[0148] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0149] In some embodiments, the battery cell also includes a separator located between the positive and negative electrode plates. The separator has a permeability of 450 s / 100cc to 650 s / 100cc. A higher permeability value indicates poorer permeability, which on the one hand improves the transport of lithium ions in the separator, reduces overall impedance, and improves kinetic and cycle performance; on the other hand, it can also play a partial role in isolation, preventing the transition metal generated after the lithium-containing transition metal oxide is destroyed from reaching the positive electrode and avoiding transition metal ions from passing through the separator to the negative electrode, thus affecting the SEI film.
[0150] As an example, the air permeability of the separator is 450 s / 100cc, 500 s / 100cc, 520 s / 100cc, 540 s / 100cc, 560 s / 100cc, 500 s / 100cc, 580 s / 100cc, 600 s / 100cc, 650 s / 100cc, and any value within either of these ranges.
[0151] The test method for the air permeability of the separator membrane includes: taking a discharged battery cell (discharged to 0% SOC at 0.33C current), disassembling the battery cell, removing the separator membrane, soaking it in DMC (dimethyl carbonate) for 4 hours to remove residual electrolyte and lithium salt, and then drying it in an oven to obtain the separator membrane. Measurement is performed using a Gurly MODEL 4110N air permeability meter. The separator membrane is laid flat, and a smooth, oil-free area is placed on the air outlet of the air compressor cylinder of the air permeability meter. It is then tightened and fixed in place. After fixing the separator membrane in the position, the weight of the cylinder floating on the liquid compresses the air inside the cylinder, resulting in a pressure difference of 1.23 kPa across the separator membrane. The test area is one square inch (approximately 6.45 cm²). 2 As air passes through the sample, the cylinder falls smoothly. The time required for 100cc of air to pass through the separator membrane is measured, which is the air permeability (unit: s / 100cc).
[0152] In this application, positive and negative electrode sheets are stacked sequentially, and a separator is placed between the positive and negative electrode sheets to provide isolation, resulting in a bare cell. Alternatively, a bare cell can be obtained after stacking or further winding. The bare cell is placed in an outer packaging, electrolyte is injected, and then it is sealed to obtain a battery cell.
[0153] In some embodiments, the battery cell also includes an outer packaging that can be used to encapsulate electrode assemblies.
[0154] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0155] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 This is a schematic diagram of a battery cell 5 according to one embodiment of this application.
[0156] In some implementations... Figure 2 yes Figure 1 The exploded view of the battery cell 5 according to one embodiment of this application is shown below. Figure 2 The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can cover the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The number of electrode assemblies 52 contained in a single battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.
[0157] In some implementations, individual battery cells can be assembled into a battery module. The number of individual battery cells contained in a battery module can be one or more, and the specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0158] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0159] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0160] In some embodiments, the battery modules described above can also be assembled into a battery device. The number of battery modules contained in the battery device can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery device.
[0161] Figure 4 This is a schematic diagram of a battery device according to one embodiment of this application. Figure 5 yes Figure 4 An exploded view of a battery device according to an embodiment of this application is shown. (Refer to...) Figure 4 and Figure 5 The battery device 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper battery box 2 and a lower battery box 3, with the upper battery box 2 covering the lower battery box 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0162] In addition, this application also provides an electrical device, which includes at least one of the battery device, battery module, or battery device provided in this application. The battery device, battery module, or battery device can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0163] As an electrical device, a battery device, battery module, or battery cell can be selected according to its usage requirements.
[0164] Figure 6 This is a schematic diagram of a battery device according to an embodiment of this application, used as a power source for an electrical device. Please refer to [link / reference]. Figure 6 The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the device's requirements for long-cycle and high-energy-density battery devices, battery devices or battery modules can be used.
[0165] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a battery as their power source.
[0166] Example The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0167] Preparation method of lithium manganese iron phosphate A-1: (1-1) Take 29.5 kg of manganese tetroxide, 58.3 kg of iron phosphate, 40.2 kg of lithium dihydrogen phosphate, 14.3 kg of lithium carbonate, 0.58 kg of titanium dioxide, and 6.4 kg of glucose into a ball mill jar, add ultrapure water to form a raw slurry with a solid content of 42%. Pour the slurry into a ball mill and mix thoroughly, then transfer it to a sand mill at 800 rpm. When the slurry particle size reaches 0.5 μm, transfer it to a centrifugal spray tower for spraying. Control the inlet air temperature at 250℃ and the outlet air temperature at 90℃ to obtain the first spray-dried material. Sinter the spray-dried material at 560℃ under a nitrogen atmosphere for 10 h to obtain a sintered sample.
[0168] (1-2) Take 100 kg of the first-burned sample obtained in step (1-1), 5.5 kg of glucose, and 4.0 kg of polyethylene glycol (molecular weight 6000) and pour them into a ball mill jar. Add ultrapure water for dispersion. After complete dispersion, control the solid content of the slurry to 42%. When the particle size of the slurry is 0.32 μm after sand milling, transfer it to a centrifugal spray tower for spraying. Control the inlet air temperature to 250℃ and the outlet air temperature to 90℃ to obtain the second spray-dried material. Sinter the spray-dried second material at 750℃ under a nitrogen atmosphere for 12 h to obtain the second-burned sample.
[0169] (1-3) The calcined sample obtained in step (1-2) is placed in an air jet mill, the air pressure is controlled at 0.25 MPa and the grading frequency is 75 Hz. The resulting air jet material is then sieved and demagnetized to obtain the final product A-1, which has a manganese molar ratio of 0.5 for lithium manganese iron phosphate and contains the doping element Ti.
[0170] Lithium-containing transition metal oxides (LiNi) 0.6 Co 0.1 Mn 0.3 Preparation method of O2)B-1: (2-1) Prepare a metal salt solution by mixing nickel sulfate, cobalt sulfate and manganese sulfate in a stoichiometric ratio of (6:1:3), prepare a sodium hydroxide solution as a precipitant, and prepare an ammonia solution as a complexing agent; (2-2) The mixed salt solution prepared in step (2-1), the precipitant and the complexing agent are added to the reaction vessel. The co-precipitation reaction is carried out under the condition of controlling the reaction temperature at 65°C and pH at 12 for 20 hours. The single crystal precursor material is then obtained by filtration, washing and drying. (2-3) The precursor obtained in step (2-2) and lithium carbonate are thoroughly mixed in a certain proportion to obtain a mixture, which is then calcined in an oxygen atmosphere to obtain a doped matrix material; (2-4) The doped matrix material obtained in step (2-3) and the transition metal sulfate are thoroughly mixed in a certain proportion and sintered again under a certain atmosphere at a sintering temperature of 880℃ to obtain single crystal particles (LiNi).0.6 Co 0.1 Mn 0.3 O2), the volume average particle size Dv50 of the single crystal particles is 3.0 μm.
[0171] Example 1 This embodiment provides a lithium-ion battery cell, and the preparation method is as follows: (1) Preparation of positive electrode sheet A conductive undercoat with a thickness of 1.5 μm is coated on both surfaces of a 13 μm thick aluminum foil for positive current collector (the mass ratio of binder to conductive agent in the conductive undercoat is 2:1).
[0172] A positive electrode active material, carbon nanotubes, and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97:2:1, and then N-methylpyrrolidone solvent was added. After thorough mixing, a positive electrode slurry with a solid content of 60% was prepared. This positive electrode slurry was coated onto a conductive undercoat, and then dried, cold-pressed, and slit to obtain the positive electrode sheet. In the positive electrode active material, the mass ratio of lithium manganese iron phosphate particles to lithium-containing transition metal oxide particles was 4:6. All lithium-containing transition metal oxide particles were single-crystal particles, and the surface of the lithium manganese iron phosphate particles had a carbon coating layer. In the positive electrode sheet, the single-sided areal density of the positive electrode film was 320 mg / 1540 mm². 2 The single-sided compaction density of the positive electrode film is 2.90 g / cm³. 3 .
[0173] (3) Preparation of negative electrode sheet Artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 97:1:1:1, and then deionized water was added. The mixture was thoroughly stirred and homogenized to prepare a negative electrode slurry with a solid content of 60%. The negative electrode slurry was coated onto both sides of a copper foil current collector, and after drying, cold pressing, and slitting, the negative electrode sheet was obtained. The artificial graphite had a Dv50 of 12 μm, and the single-sided areal density of the negative electrode sheet was 180 mg / 1540 mm². 2 .
[0174] (4) Separating membrane A 7μm thick polyethylene film is used as the base film, and ceramic layers with a thickness of 1μm are coated on both sides as isolation films. The porosity of the isolation film is 45%, and the air permeability is 550s / 100cc.
[0175] (5) Electrolyte A mixture of methyl ethyl carbonate, diethyl carbonate, and ethylene carbonate was prepared. Lithium hexafluorophosphate, lithium difluorosulfonyl imide, vinylene carbonate, 1,3-propanesulfonate lactone, and lithium difluorophosphate were dissolved in this solution to obtain an electrolyte. In this electrolyte, the mass percentages of methyl ethyl carbonate, diethyl carbonate, ethylene carbonate, lithium hexafluorophosphate, lithium difluorosulfonyl imide, lithium difluorosulfonyl imide, ethyleneene carbonate, ethylene carbonate, 1,3-propanesulfonate lactone, and lithium difluorophosphate were 2%.
[0176] (6) Battery assembly The positive electrode, separator, and negative electrode are stacked in sequence and then wound to obtain a wound battery cell. The battery cell is placed in a square aluminum shell, and the electrolyte prepared above is added. After processes such as encapsulation, standing, formation, and aging, the lithium-ion battery cell of Example 1 is obtained.
[0177] Example 2 Example 2 provides a lithium-ion battery cell, which differs from Example 1 in that: In the positive electrode active material, the mass ratio of lithium manganese iron phosphate particles to lithium-containing transition metal oxide particles is 2:8. Example 3 Example 3 provides a lithium-ion battery cell, which differs from Example 1 in that: In the positive electrode active material, the mass ratio of lithium manganese iron phosphate particles to lithium-containing transition metal oxide particles is 4.5:5.5. Examples 4-9 Examples 4-9 provide a lithium-ion battery cell, which differs from Example 1 in that: The preparation method of lithium manganese iron phosphate material was adjusted to obtain A-2 to A-5. The molar ratio of manganese source and iron source in the raw materials was adjusted to achieve the molar ratio of manganese in lithium manganese iron phosphate, resulting in A-6 to A-7. The specific adjustment parameters are shown in Table 1.
[0178] Examples 10-12 Examples 10-12 adjust the preparation method of lithium-containing transition metal oxide materials to obtain B-2 to B-4. The specific adjustment parameters are shown in Table 1.
[0179] Comparative Examples 1-2 Comparative Examples 1-2 provide a lithium-ion battery cell, which differs from Example 1 in that: By adjusting the preparation method of lithium manganese iron phosphate materials, A-8 and A-9 were obtained. The preparation conditions of some lithium-ion battery cells in Examples 1-12 and Comparative Examples 1-2 are shown in Table 1.
[0180] Table 1. Preparation parameters of lithium manganese iron phosphate and lithium-containing transition metal oxides
[0181] Test case The lithium-ion battery cells prepared in Examples 1 to 12 and Comparative Examples 1 to 2 were tested. The test results are shown in Table 2. The specific test methods are as follows: 1. Parameters of a single lithium-ion battery cell (1) Particle size distribution of lithium manganese iron phosphate After discharging the battery cell (discharging to 0% SOC at 0.33C current), the positive electrode sheet was removed and soaked in DMC (dimethyl carbonate) for 4 hours to remove residual electrolyte and lithium salt. It was then dried in an oven to obtain the positive electrode sheet. A portion of the positive electrode sheet was cut to obtain the first positive electrode sheet sample. The positive electrode film was cut along the thickness direction of the positive electrode sheet using an argon ion beam (for example, a Leica EM TIC 3X CP device can be used, operating voltage: 6kV, operating time: 6h). After exposing the cut surface, a scanning electron microscope (for example, a Hitachi SU8230 device can be used, operating voltage: 3kV, beam current: high, probe model: U (LA100), working distance <5mm) was used to observe the cut surface along the thickness direction of the positive electrode sheet. Images were acquired using a field emission scanning electron microscope (FEM) at non-edge locations within the cross-section of the positive electrode film (after observing the edge of the positive electrode sheet under the SEM, the field of view was adjusted to the center of the sample) in secondary electron mode. These images were obtained at various magnifications (2kx for ternary particles and 30kx for lithium manganese iron phosphate particles). The elements in the particles were then analyzed using energy-dispersive X-ray spectroscopy (EDS). Particles rich in nickel and cobalt were labeled as lithium transition metal oxide particles, and particles rich in iron were labeled as lithium manganese iron phosphate particles.
[0182] Based on the aforementioned method, lithium-containing transition metal oxide particles and lithium manganese iron phosphate particles were identified. Then, the lithium manganese iron phosphate particles in the electron microscope images were analyzed using ImageJ software (1.46r, Win64 version). The "Feret diameter" analysis function in ImageJ was used to analyze the area of the particles in the cross-section along the electrode thickness direction of the positive electrode film. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter obtained from the analysis represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. The "How to Use ImageJ Software" section is detailed in the specific implementation method and will not be repeated here.
[0183] Following the above method, 10 non-overlapping scanning electron microscope (SEM) images (5μm × 4μm for counting lithium manganese iron phosphate particles) were acquired for each positive electrode, and the particle size of 1500 particles was counted. The 1500 lithium manganese iron phosphate particles were arranged in ascending order of particle size to obtain the number of lithium manganese iron phosphate particles with a particle size greater than or equal to 50nm and less than or equal to 120nm, and the number of lithium manganese iron phosphate particles with a particle size greater than 120nm and less than or equal to 600nm. Based on the total number of lithium manganese iron phosphate particles, the percentage of lithium manganese iron phosphate particles with a particle size greater than or equal to 50nm and less than or equal to 120nm, and the percentage of lithium manganese iron phosphate particles with a particle size greater than 120nm and less than or equal to 600nm were then obtained.
[0184] (2) The Dn10 value of lithium-containing transition metal oxide particles In the aforementioned SEM images of the cross-section of the positive electrode, lithium-containing transition metal oxide particles were identified (at least 10 fields of view were acquired for each positive electrode, with the field size for lithium-containing transition metal oxide particles being 150 μm × 120 μm). The lithium-containing transition metal oxide particles in the SEM images were analyzed using ImageJ software (1.46r, Win64 version). The "Feret diameter" analysis function in ImageJ was used to analyze the area of the particles in the cross-section along the thickness direction of the positive electrode film. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret" parameter obtained from the analysis represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. The usage of ImageJ software is described above and will not be repeated here.
[0185] The particle size of lithium transition metal oxide particles was obtained by the aforementioned method. The particle sizes of 1500 lithium transition metal oxide particles were arranged in ascending order, and the cumulative distribution curve of the number of lithium transition metal oxide particles was plotted. Dn10 refers to the particle size corresponding to the cumulative number distribution of particles reaching 10% in the cumulative distribution curve of the number of lithium transition metal oxide particles.
[0186] 2. Performance of lithium-ion battery cells (1) Volumetric energy density ① At 25℃, discharge the battery at a constant current rate of 0.33C to 2.5V and let it stand for 5 minutes; ② Charge the battery at a constant current rate of 0.33C to 4.4V, then charge it at a constant voltage until the current drops to 0.05C, and let it stand for 5 minutes; ③ Discharge the battery again at a constant current rate of 0.33C to 2.5V, record the discharge capacity, and let it stand for 5 minutes; Steps ② and ③ constitute one charge-discharge cycle. Record the discharge energy obtained in the second cycle as E; measure the battery dimensions using vernier calipers and calculate the volume V. The volumetric energy density K = E / V.
[0187] (2) Cyclic performance The number of charge / discharge cycles when the battery capacity decays to 80% at 2.5V~4.4V is determined as follows: ① At 25℃, discharge the battery at a constant current rate of 0.33C to 2.5V and let it rest for 5 minutes; ② Charge the battery at a constant current rate of 0.33C to 4.4V, then charge it at a constant voltage until the current drops to 0.05C, and let it rest for 5 minutes; ③ Discharge the battery again at a constant current rate of 0.33C to 2.5V, record the discharge capacity, and let it rest for 5 minutes; Steps ② and ③ constitute one charge / discharge cycle. The discharge capacity obtained in the second cycle is recorded as the initial capacity (C0). Subsequent cycle procedures are as follows: At 45℃, charge the battery at a constant current rate of 1C0 to 4.4V, then charge it at a constant voltage until the current drops to 0.05C, let it rest for 5 minutes, and then discharge the battery again at a constant current rate of 1C0 to 2.5V. This constitutes one charge / discharge cycle. Perform charge / discharge tests on the battery according to this procedure. When the capacity reaches 0.8C0, record the number of battery cycles.
[0188] Table 2. Parameters and performance test results of individual battery cells.
[0189] As can be seen from Tables 1 and 2, in Comparative Example 1, the proportion of small-particle (50nm~120nm particle size) lithium manganese iron phosphate particles is too high, which significantly affects the battery's cycle performance. In Comparative Example 2, the proportion of small-particle (50nm~120nm particle size) lithium manganese iron phosphate particles is too low, the capacity of lithium manganese iron phosphate cannot be fully utilized, and the battery's energy density is low.
[0190] Compared to Comparative Examples 1 and 2, in Examples 1 to 12, for batteries containing a mixture of lithium transition metal oxide particles and lithium manganese iron phosphate particles, the positive electrode active material satisfies the following: the molar ratio of manganese in lithium manganese iron phosphate is 0.3 to 0.7, the mass content of lithium transition metal oxide is 55% to 80% (compared to the total mass of lithium manganese iron phosphate and lithium transition metal oxide materials), and in the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%, which can make the battery have a higher energy density and significantly improved cycle performance.
[0191] A comparison of Examples 1 to 3 shows that the more lithium-containing transition metal oxides are added, the higher the volumetric energy density and the better the cycle performance of the battery. However, the cost of the battery is also higher. In this application, based on comprehensive consideration, while satisfying the condition that "the molar ratio of manganese iron phosphate is 0.3 to 0.7 and the number of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%", the mass ratio of lithium-containing transition metal oxides is adjusted to 60% to 80%, which can further balance the cost, energy density and cycle performance of the battery.
[0192] A comparison of Examples 1 and 4-7 shows that the smaller the percentage of particles with a diameter of 50nm to 120nm, the better the cycle performance, while the larger the percentage, the greater the volumetric energy density. Therefore, in this application, controlling the percentage of lithium manganese iron phosphate particles with a diameter greater than or equal to 50nm and less than or equal to 120nm to 5% to 25% can balance the energy density and cycle performance of the battery.
[0193] A comparison of Examples 1, 8, and 9 shows that the higher the molar ratio of manganese in lithium iron phosphate, the higher the energy density of the battery, but the worse the cycle performance. Therefore, this application, while satisfying the requirement that "the mass content of lithium transition metal oxide is 55%~80%, and the number of lithium iron phosphate particles with a particle size greater than or equal to 50nm and less than or equal to 120nm is 2%~35%", controls the molar ratio of manganese in lithium iron phosphate to be 40%~60%, which can further balance the energy density and cycle performance of the battery.
[0194] A comparison of Examples 2 and 10-12 shows that, under the condition that the molar ratio of manganese in lithium iron phosphate is 0.3-0.7, the mass content of lithium transition metal oxide is 55%-80%, and the number of lithium iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2%-35%, controlling the Dn10 range of the primary particles containing lithium transition metal oxide to 0.8 μm-2 μm can further improve the cycle performance of the battery while meeting the energy density requirements.
[0195] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A battery cell, characterized in that, The device includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. The positive electrode film includes a positive electrode active material, which includes lithium manganese iron phosphate particles and lithium-containing transition metal oxide particles. The lithium-containing transition metal oxide includes nickel, cobalt, and manganese. The manganese molar ratio of the lithium manganese iron phosphate is 0.3 to 0.7, and the manganese molar ratio is the ratio of the number of moles of manganese to the total number of moles of manganese and iron. Based on the mass of the positive electrode active material, the mass content of the lithium-containing transition metal oxide is 55% to 80%. In the cross-section of the positive electrode film along the thickness direction of the positive electrode, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size greater than or equal to 50 nm and less than or equal to 120 nm is 2% to 35%.
2. The battery cell according to claim 1, characterized in that, Based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size of 50nm~120nm is 5%~25%.
3. The battery cell according to claim 1 or 2, characterized in that, The manganese molar ratio of the lithium manganese iron phosphate is 0.4~0.
6.
4. The battery cell according to claim 1, characterized in that, In the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size greater than 120 nm and less than or equal to 600 nm is 65% to 98%. Based on the total number of lithium manganese iron phosphate particles, the total proportion of lithium manganese iron phosphate particles with a particle size of 50 nm to 120 nm and lithium manganese iron phosphate particles with a particle size greater than 120 nm and less than or equal to 600 nm is less than or equal to 100%.
5. The battery cell according to claim 2, characterized in that, In the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, based on the total number of lithium manganese iron phosphate particles, the proportion of lithium manganese iron phosphate particles with a particle size greater than 120 nm and less than or equal to 600 nm is 75% to 95%. Based on the total number of lithium manganese iron phosphate particles, the total proportion of lithium manganese iron phosphate particles with a particle size of 50 nm to 120 nm and lithium manganese iron phosphate particles with a particle size greater than 120 nm and less than or equal to 600 nm is less than or equal to 100%.
6. The battery cell according to claim 1, characterized in that, Based on the mass of the positive electrode active material, the mass percentage of lithium manganese iron phosphate is 20% to 45%.
7. The battery cell according to claim 1, characterized in that, The lithium manganese iron phosphate particles contain metal doping elements, including at least one of Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg.
8. The battery cell according to claim 7, characterized in that, The metal doping element includes at least one of Al, Mg, Ti, V, and Nb.
9. The battery cell according to claim 7, characterized in that, Based on the mass of the lithium manganese iron phosphate particles, the doping amount of the metal dopant is 1000ppm~12000ppm.
10. The battery cell according to claim 7, characterized in that, Based on the mass of the lithium manganese iron phosphate particles, the doping amount of the metal dopant is 3000ppm-8000ppm.
11. The battery cell according to claim 1, characterized in that, The chemical formula of lithium manganese iron phosphate is Li. m1 Fe x1 Mn y1 M1 b1 P z1 Q1 c1 O n1 N1 d1 Wherein, 0.8≤m1≤1.2, 0<x1<1, 0<y1<1, 0.9≤x1+y1≤1, 0.95≤z1≤1, 3.5≤n1≤4, 0≤b1≤0.1, 0≤c1≤0.1, 0≤d1≤0.1; wherein, M1 includes one or more of Al, Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, and Mg, Q1 includes one or more of B, S, Si, and N, and N1 includes one or more of S, F, Cl, and Br.
12. The battery cell according to claim 1, characterized in that, The surface of the lithium manganese iron phosphate particles also contains a carbon coating layer, the thickness of which is 2nm~20nm.
13. The battery cell according to claim 12, characterized in that, Based on the total mass of the lithium manganese iron phosphate particles, the carbon coating layer accounts for 0.5% to 3% of the total mass.
14. The battery cell according to claim 1, characterized in that, The lithium-containing transition metal oxide particles include single-crystal particles.
15. The battery cell according to claim 14, characterized in that, In the cross-section of the positive electrode film layer along the thickness direction of the positive electrode sheet, the Dn10 of the lithium-containing transition metal oxide particles is 0.5μm~2.0μm; where Dn10 refers to the particle size corresponding to the cumulative number distribution of particles reaching 10% in the cumulative number distribution curve of the lithium-containing transition metal oxide particles.
16. The battery cell according to claim 14, characterized in that, In the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn10 of the lithium-containing transition metal oxide particles is 0.8 μm to 2 μm.
17. The battery cell according to claim 15, characterized in that, In the cross-section of the positive electrode film layer along the thickness direction of the positive electrode sheet, the Dn50 of the lithium-containing transition metal oxide particles is 1.0 μm to 4.0 μm. Here, Dn50 refers to the particle size corresponding to the cumulative number distribution of particles reaching 50% in the cumulative distribution curve of the number of lithium-containing transition metal oxide particles.
18. The battery cell according to claim 15, characterized in that, In the cross-section of the positive electrode film along the thickness direction of the positive electrode sheet, the Dn50 of the lithium-containing transition metal oxide particles is 2.0 μm to 3.5 μm.
19. The battery cell according to claim 1, characterized in that, In the lithium-containing transition metal oxide, the molar percentage of nickel is 0.55 to 0.8% based on the total molar number of nickel, cobalt, and manganese.
20. The battery cell according to claim 1, characterized in that, In the lithium-containing transition metal oxide, the molar percentage of nickel is 0.6 to 0.75, based on the total molar number of nickel, cobalt, and manganese.
21. The battery cell according to claim 1, characterized in that, In the lithium-containing transition metal oxide, based on the total molar number of nickel, cobalt, and manganese, the molar percentage of cobalt is 0.05~0.3; or / and, in the lithium-containing transition metal oxide, based on the total molar number of nickel, cobalt, and manganese, the molar percentage of manganese is 0.15~0.
4.
22. The battery cell according to claim 21, characterized in that, The lithium-containing transition metal oxide further includes modifying elements, which include one or more elements selected from Zr, La, Sr, Sb, Al, and W.
23. The battery cell according to claim 1, characterized in that, The positive electrode film layer also includes a conductive agent, which includes at least one of carbon nanotubes, graphite sheets, conductive carbon black, and Ketjen black.
24. The battery cell according to claim 23, characterized in that, The conductive agent includes carbon nanotubes.
25. The battery cell according to claim 23, characterized in that, The positive electrode film layer further includes a binder and a conductive agent. In the positive electrode film layer, the mass ratio of the positive electrode active material, the binder, and the conductive agent is (92~99):(0.5~3):(0.5~3).
26. The battery cell according to claim 1, characterized in that, The areal density of the positive electrode film layer is 200 mg / 1540 mm². 2 ~400mg / 1540mm 2 .
27. The battery cell according to claim 1, characterized in that, The areal density of the positive electrode film layer is 240 mg / 1540 mm². 2 ~300mg / 1540mm 2 .
28. The battery cell according to claim 1, characterized in that, The single-sided compaction density of the positive electrode film is 2.40 g / cm³. 3 ~3.30g / cm 3 .
29. The battery cell according to claim 1, characterized in that, The single-sided compaction density of the positive electrode film is 2.70 g / cm³. 3 ~3.00g / cm 3 .
30. The battery cell according to claim 1, characterized in that, The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, wherein the single-sided areal density of the negative electrode film layer is 110 mg / 1540 mm². 2 ~180mg / 1540mm 2 .
31. The battery cell according to claim 30, characterized in that, The areal density of the negative electrode film layer is 110 mg / 1540 mm². 2 ~150mg / 1540mm 2 .
32. The battery cell according to claim 30, characterized in that, The compaction density of the negative electrode film is 1.2 g / cm³. 3 ~1.7g / cm 3 .
33. The battery cell according to claim 1, characterized in that, The battery cell also includes an electrolyte, which comprises chain carbonates and cyclic carbonates.
34. The battery cell according to claim 33, characterized in that, Based on the mass of the electrolyte, the mass percentage of chain carbonates is 55% to 65%, and the mass percentage of cyclic carbonates is 20% to 30%.
35. The battery cell according to claim 34, characterized in that, The chain carbonates include methyl ethyl carbonate and diethyl carbonate, and the cyclic carbonates include ethylene carbonate.
36. The battery cell according to claim 33, characterized in that, The electrolyte further includes a first film-forming additive, which includes one or more of lithium difluorophosphate and tris(trimethylsilane) phosphate.
37. The battery cell according to claim 36, characterized in that, Based on the mass of the electrolyte, the mass percentage of the first film-forming additive is 1% to 4%.
38. The battery cell according to claim 37, characterized in that, The electrolyte further includes a second film-forming additive, which includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propanesulfonate lactone, ethylene disulfate, and butene sulfite.
39. The battery cell according to claim 38, characterized in that, Based on the mass of the electrolyte, the mass percentage of the second film-forming additive is 0.2% to 2%.
40. The battery cell according to claim 33, characterized in that, The electrolyte includes one or more of lithium hexafluorophosphate and lithium difluorosulfonylimide.
41. The battery cell according to claim 33, characterized in that, The electrolyte comprises lithium hexafluorophosphate and difluorosulfonyl imide salt.
42. The battery cell according to claim 40, characterized in that, Based on the mass of the electrolyte, the lithium hexafluorophosphate content is 5%-10%.
43. The battery cell according to claim 40, characterized in that, Based on the mass of the electrolyte, the mass content of the lithium difluorosulfonamide is 0.1%-2%.
44. The battery cell according to claim 40, characterized in that, The positive electrode sheet also includes a conductive undercoating layer, which is located between the positive current collector and the positive electrode film layer.
45. The battery cell according to claim 1, characterized in that, The battery cell also includes a separator membrane located between the positive electrode and the negative electrode, and the separator membrane has an air permeability of 450 s / 100cc-650 s / 100cc.
46. A battery device, characterized in that, Includes the battery cell described in any one of claims 1 to 45.
47. An electrical appliance, characterized in that, Includes the battery device as described in claim 46.
Citation Information
Patent Citations
Positive electrode active material and positive electrode plate of lithium ion battery, and preparation method and application of positive electrode active material and positive electrode plate
CN116864677A
Positive electrode active material, positive electrode, battery, and device
CN118231653A